A low-complexity low-cost phased array / M. Askari and H. Kaabi - Askari, M.; Kaabi, H. (UiTM Press, 2017)
A low-complexity low-cost structure is proposed for phased array systems. It is shown that the change in the phase reference of the antenna array leads to a less complexity system, which is very essential for RFIC processes. There is no need to use the bulky and lossy "gain control" circuits. Therefore, the complex "magnitude tapering" algorithms, which are used to reduce the sidelobes level of array patterns, are simply implemented in the proposed structure. The phase shifters of the proposed scheme are structurally simpler than those of the conventional phased arrays. The comparison between the proposed and the conventional phased array structures in such areas as array pattern, tapering, and directivity is studied using simulation.